Sahwira mukuru anokunda weropa: social networks and precarity in the narratives of Zimbabwean undocumented waitrons - Matina, Sostina Spiwe (My University, 2017)
This study speaks to a broader literature on the precarity of service employees and undocumented migrants. Within this literature we see lives characterised by low paying jobs and a lack of social protection. Narratives and in-depth interviews were used in-order to find out how undocumented Zimbabwean waitrons in Johannesburg employ social networks to mitigate economic precarity. In examining Zimbabwean waitrons working the Johannesburg’s precarious hospitality sector, I found evidence that demonstrates the importance of social networks but demands we take a more nuanced look at the ways in which they work. More specifically, there are not only straight social connections, but sexual networks and, religious networks, and – perhaps most importantly – overt patterns of disconnections. While social networks can invariably play an important role in migrants’ (and others’) success, they are not without potential risks. In light of this, this study sought to systematically investigate the role of social networks in mitigating precarity. This study adds to emerging field of social networks of marginalised groups and a growing literature on migrant integration in the social and economic environments of the global south.
A research report submitted to the Faculty of Humanities University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Migration and Displacement), 2017
Keywords: Foreign workers--South Africa--Johannesburg; Migrant labor--South Africa--Johannesburg; Immigrants|zSouth Africa|xSocial conditions